Perlindungan Hak-Hak Perempuan Dalam Hukum Hindu Perspektif Hak Asasi Manusia - Gunawan, Wayan; Santika, Kade Ayu (Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2025)
This article discusses the protection of women's rights in Hindu law from a Human Rights (HAM) perspective. In the context of Hindu society which has developed within strong traditions and culture, women's rights are often faced with challenges caused by normative interpretations of sacred texts and customs. Even though Hindu teachings contain values ​​of respect for women, the implementation of women's rights in social life is sometimes not fully in line with modern human rights principles. This article analyzes various provisions in Hindu law related to the position of women, including rights in marriage, inheritance, and protection against violence. Additionally, this article explores efforts to balance Hindu legal traditions with the development of more progressive human rights values, to ensure better protection of women's rights in contemporary Hindu society. Through this approach, it is hoped that awareness will be created about the importance of integration between religious law and human rights in supporting gender equality.